Analysis and Performance Assessment of the Whole Genome Bisulfite Sequencing Data Workflow: Currently Available Tools and a Practical Guide to Advance DNA Methylation Studies. Issue 3 (22nd January 2022) - Gong, Ting; Borgard, Heather; Zhang, Zao; Chen, Shaoqiu; Gao, Zitong; Deng, Youping
Abstract: DNA methylation is associated with transcriptional repression, genomic imprinting, stem cell differentiation, embryonic development, and inflammation. Aberrant DNA methylation can indicate disease states, including cancer and neurological disorders. Therefore, the prevalence and location of 5‐methylcytosine in the human genome is a topic of interest. Whole‐genome bisulfite sequencing (WGBS) is a high‐throughput method for analyzing DNA methylation. This technique involves library preparation, alignment, and quality control. Advancements in epigenetic technology have led to an increase in DNA methylation studies. This review compares the detailed experimental methodology of WGBS using accessible and up‐to‐date analysis tools. Practical codes for WGBS data processing are included as a general guide to assist progress in DNA methylation studies through a comprehensive case study. Abstract : DNA methylation is an epigenetic mechanism controlling gene expression. Aberrant DNA methylation can indicate disease states, including cancer. This review analyzes the common methods used for studying DNA methylation. It compares the detailed experimental methodology of Whole‐genome bisulfite sequencing using accessible and up‐to‐date analysis tools. It provided a step‐by‐step case study to guide new researchers in chromosomal aberrations research.